A new approach to construct three dimensional segregated graphene structures in rubber composites for enhanced conductive, mechanical and barrier properties. Issue 12 (9th March 2016) - Lin, Yong; Liu, Shuqi; Liu, Lan
Abstract : A novel pre-construction method was reported for the first time to fabricate conductive rubber composites with a conductive 3D-graphene segregated network. Abstract : Styrene butadiene rubber/graphene (SBR3GE-DH) composites with a segregated graphene network, synchronously having high electrical conductivity, mechanical strength and gas barrier properties, were fabricated for the first time using a pre-construction strategy combined with static hot pressing. A "three dimensional graphene (3D-GE) network" with percolation conductive paths was efficiently constructed with an extremely low percolation threshold of 0.55 vol%. Remarkably, a conductivity of 0.033 S m −1 at a 3D-GE content of 1.66 vol% was 8 orders of magnitude higher than that of the sheet-like GE-based composites (SBRGE) prepared by conventional latex compounding. All those outstanding properties were attributable to the well-constructed "3D-GE segregated networks" in the SBR matrix and the strong interfacial adhesion between 3D-GE and the SBR matrix resulting from the geometric confinement of 3D-GE networks. Such performances make SBR3GE-DH composites very competitive for potential applications in high conductive sealing gaskets in the aerospace industry, sealed packages, and gas transport and storage devices.